At a fruit market where no sales tax is charged, Abe paid ₱1.90 for 1 pear and 3 apples; Joan paid ₱1.60 for 1 pear, 1 apple, and 1 orange; and Latonya paid ₱1.70 for 2 apples and 1 orange. If each person paid the same amount per pear, the same amount per apple, and the same amount per orange, what amount did each person pay for each apple?

2

Answers

2014-11-25T17:43:41+08:00
Let 'x' be the cost of 1 apple
     'y' be the cost of 1 pear
     'z' be the cost of 1 orange
----------------------------------
Abe paid Php1.90 for 1 pear and 3 apples
y + 3x = 1.90   ------equation 1
---------------------------------
Joan paid Php1.60 for 1 pear, 1 apple and 1 orange
x + y + z = 1.60   -----equation 2
-------------------------------
Latonya paid Php1.70 for 2 apples and 1 orange
2x + z = 1.70   ----equation 3
---------------------------------
express y and z in terms of x
from equation 1
y + 3x = 1.90
y = -3x + 1.90    ----equation 1'

from equation 3
2x + z = 1.70
z = -2x + 1.70   ----equation 3'
---------------------------------
Substitute equations 1' and 3' to equation 2
x + y + z = 1.60
x + (-3x + 1.90) + (-2x + 1.70) = 1.60
x - 3x + 1.90 - 2x + 1.70 = 1.60
x - 3x - 2x = 1.60 - 1.70 - 1.90
-4x = -2
x = 0.50
------------------------------
Substitute x=0.50 to equations 1' and 3'
y = -3x + 1.90
y = -3(0.50) + 1.90
y = -1.50 + 1.90
y = 0.40

z = -2x + 1.70
z = -2(0.50) + 1.70
z = -1 + 1.70
z = 0.70
------------------------------
Therefore apple costs Php0.50 each
                   pear costs Php0.40 each and
                   orange costs Php0.70 each
0
lol we have different values but same answer when you substitute o_O
2014-11-25T18:29:40+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let:
x-pear
y-apples
z-orange

x+3y=1.9
x+y+z=1.6
2x+z=1.7

Lets find the value of x in the first equation
x=1.9-3y
Lets find the value of z in the third equation.
z=1.7-2x
z=1.7-3.8+6y
z=-2.1+6y
Substitute the value on the 2nd equation.
1.9-3y+y-2.1+6y=1.6
4y-0.2=1.6
4y=1.8
y=0.45

Substitute the value of x:
x=1.9-3(0.45)
x=1.9-1.35
x=0.55

Substitute the value of x
z=1.7-2(0.55)
z=1.7-1.1
z=0.6

Hope this helps =)
0